UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN TANAMAN JOHAR (Cassia siamea Lamk.) DARI BEBERAPA TINGKAT KEPOLARAN PELARUT - Fitriah Fitriah; Mappiratu Mappiratu; Prismawiryanti Prismawiryanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
A research about antibacterial activity test of johar plant leaf extract (Cassia siamea Lamk.) using several levels of solvent polarity has been implemented. This study aims to determine whether the antibacterial compounds in the leaves is polar, non-polar or semi-polar, and to determine the highest inhibition level of johar leaf extract on both the gram-negative bacteria (Escherichia coli and Shigella dysenteriae) and gram-positive (Staphylococcus aureus and Micrococcus luteus). The maceration method was used in this research with 3 levels of solvent polarity namely non-polar, semi-polar and polar. The bacterial activity test was done with diffusion method. The results showed that the johar leaf contains antibacterial compounds which are polar and semi-polar. The highest inhibition level was obtained at johar leaf ethanol extract for Staphylococcus aureus, Escherichia coli, Micrococcus luteu and Shigella dysentriae of 14.9, 12.9, 12, and 7.2 mm, respectively.Keywords: Antibacterial, Inhibition Level, Johar Leaf Extract